Evaluasi Pertumbuhan dan Produksi Fodder Hidroponik Millet (Panicum milliaceum) dengan Perbedaan Intensitas Cahaya dan Umur Panen - Nur Hidayat, Anisa Ayu Rini,; Harwanto; Nur Hidayat (Universitas Islam Negeri Alauddin Makassar, 2024)
Hidroponic fodder is forage cultivation by using liquid medium which contain nutrients for growth. Plant growth is influenced by two factor, internal and external factors. Internal factors include genetic, growth hormon and age. External factors include light intensity and plant growth medium. The aim of the study was to determine the effect of light intensity and harvest age on the growth and production of fodder millet (Panicum milliaceum). The study used white millet seeds with proso millet varieties, and hydroponic media. The study used a completely randomized design with a factorial pattern (2x3). The first factor is light intensity (I) 50% and I 100%. The second factor is harvest age (U) 6, 9, and 12 days. Each treatment combination was replicated 4 times. The density of millet seeds in the media was 0.15 gram/cm² and planted for 12 days using the Deep Water Culture (DWC) hydroponic system. The significance value was tested by Duncan Multiple Range Test (DMRT). The variables measured were leaf length, leaf amount, leaf width, root length, plant height, fresh production and dry matter production. The results showed that light intensity and harvest age had a significant effect (P<0.05) on fodder growth. The results show that light intensity can increase (P<0.05) fodder height from 4.51 cm (U6), 5.35 cm (U9) and 8.43 cm (U12) while at an intensity of 5.51 cm (I1) to I2 6.13 cm (I2) and fresh production from 9,48 kg/m2 (U6), 10,04 kg/m2 (U9) and 10,12 kg/m2 (U12) while the intensity of 10,07 kg/m2 (I1) becomes 9,69 kg/m2 (I2). The study concluded that light intensity 100% (13.933 lux) and harvest age 12 day could increase fodder millet growth.